CONTRAST OF TV-SATELLITE IMAGE EDGES AND QUALITYMEASUREMENT - Al-Zuky, Ali A D; Ali, Esraa H (Al-Nahrain Journal of Science, 2018)
In this paper the TV-satellite images have been analyzed to estimate their quality by using contrast of image edges method. The edges of the image have the most important image information and details that describe its contents. The contrast of edges has been determined using Michelson formula after modifying it into two different equations based on the mentioned formula. This method has been applied to the TV-Satellite images (same image) from the same channel (Abu Dhabi) of different satellites which are Arabsat, Hotbird, and Nilesat. The results show that the image on Nilesat has the best contrast of edges in the two ways than the images on Arabsat and Hotbird.